CURRENT THEORETICAL METHODOLOGICAL PROBLEMS OF SOCIAL-PHILOSOPHICAL ANALYSIS OF ETHNICITY AND NATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article provides a comprehensive analysis of the concept of “ethnicity” in social science, examining the evolution of the discussion surrounding it since the 1970s. It highlights three main theoretical approaches to the study of ethnicity: primordialism, instrumentalism, and constructivism, elaborating on their key tenets and proponents. Special attention is paid to the development of the primordialist approach, including sociobiological and evolutionary-historical directions, as well as the concepts of L.N. Gumilev and Yu.V. Bromley, which dominated Soviet science. The article analyzes the instrumentalist approach, which emerged in response to the need to explain mass ethnic movements, and the constructivist approach, which emphasizes the role of intellectual constructions and the activities of ideologues in the formation of ethnicity. The strengths and weaknesses of each approach are critically examined, underscoring the necessity of their integration for an adequate understanding of the ethnic world picture. A significant part of the work is devoted to the problem of defining the essence and content of the terms “ethnos” and “nation,” analyzing various interpretations of these concepts in Soviet and post-Soviet social science, including discussions around the civic and ethnic interpretations of the nation. The article traces the evolution of views on nationalism as a socio-political phenomenon and ideology. In conclusion, it states the absence of a universally recognized approach to the study of these key categories in modern social science.
Keywords: ethnicity, ethnos, nation, primordialism, instrumentalism, constructivism, ethnic self-consciousness, nationalism, Soviet social science, post-Soviet social science.